2006
DOI: 10.1021/je0502041
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus for the Determination of Water Solubility in Hydrocarbon: Toluene and Alkylcyclohexanes (C6 to C8) from 30 °C to 180 °C

Abstract: An apparatus has been designed and constructed to measure mutual solubilities of (water + hydrocarbon). The solubility of water in toluene, cyclohexane, methylcyclohexane, ethylcyclohexane, and (cis + trans)-1,2-dimethylcyclohexane were determined at temperatures ranging from (30 to 180)°C. Measurements obtained for toluene show good agreement with literature values and allow us to validate this new method. As expected, increasing the temperature increases the solubilities of water in the alkylcyclohexanes. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The analytical method developed in this study exploits the relative difference in solubility of Nic and NicH + in toluene and water, respectively. With a solubility of water in toluene of 3.3 × 10 –3 mole fraction, , 6 mL of toluene absorbs a minimal amount of 3.36 μL from the water phase. The extracted Nic in the toluene phase was then introduced into a gas chromatograph coupled with a mass spectrometer for quantification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical method developed in this study exploits the relative difference in solubility of Nic and NicH + in toluene and water, respectively. With a solubility of water in toluene of 3.3 × 10 –3 mole fraction, , 6 mL of toluene absorbs a minimal amount of 3.36 μL from the water phase. The extracted Nic in the toluene phase was then introduced into a gas chromatograph coupled with a mass spectrometer for quantification.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that toluene is an effective agent for nicotine extraction in the liquid−liquid equilibrium of the nicotine/water/toluene system 20 and that, in comparison to other common solvents, toluene has the lowest water solubility. 24 Using the reported solubility of water in toluene of 3.3 × 10 −3 mole fraction, 19 we calculated that less than 0.1% by volume of water can be dissolved in the toluene extract, resulting in a similarly negligible bias error in the determination of NicH + . A high percent total Nic recovery of 92.1% (% Nic E1 = ((Nic E1 )/(Nic total )) = 92.1%) was obtained when the extraction method was tested on standard solutions of known concentrations as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Wettability alteration toward a more water-wet surface is generally accepted as the cause for increased recovery. History matching of experimental results, and modeling of field potential, is therefore performed by changing flow functions (Masalmeh et al 2014). There is, however, also a consensus that the underlying recovery mechanisms are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Solubility of water in cyclohexane. ●, this work; ○, Tsonopoulos and Wilson; ◊, Marche et al; ×, Plenkina et al; ----, model …”
Section: Resultsmentioning
confidence: 84%